Evaluation of Hash Join Operations Performance Executing on SDN Switches: A Cost Model Approach - S. Franco, Marisa; Dominico, Simone; R. Kepe, Tiago; C. P. Albini, Luiz; C. de Almeida, Eduardo; A. Z. Alves, Marco (Journal of Information and Data Management, 2022)
Distributed database systems store and manipulate data on multiple machines. In these systems, the processing cost of query operations is mainly impacted by the data access latency between machines over the network. With recent technology advances in programmable network devices, the network switches provide new opportunities for dynamically managing the network topology, enabling the data processing on these devices with the same network throughput. In this paper, we explore the programmable network switches in query processing, evaluating the processing performance of a cost model in executing the hash join operation. We assume the storage of the hash table built from outer relation and the materialization of the join probing are made in switches using advanced matching techniques similar to package inspections enabled by Ternary Content-Addressable Memories (TCAM) or SRAM via hashing. Our results show that processing the hash join operation using network switches achieved the best results compared to traditional servers, with an average time reduction of 91.82% (Query-10 from TPC-H) and 96.52% (Query-11 from TPC-H).